Proprioceptive acuity is core for back awareness in chronic low back pain: Further analysis of the content validity of the Spanish version of the Fremantle Back Awareness Questionnaire - García-Dopico, Nuria; de la Torre-Luque, Alejandro; Sitges, Carolina; Velasco-Roldán, Olga (Frontiers in Human Neuroscience, 2023)
Treatments aimed at increasing self-perception may improve chronic low back pain (CLBP) symptomatology and present novel management approaches. Consequently, it is important to have valid, complete, and reliable tools for its assessment, and to understand which variables influence altered back awareness. We aimed to evaluate the face/content validity of the Spanish version of the Fremantle Back Awareness Questionnaire (FreBAQ-S) among people with and without CLBP, and to explore additional variables suggested to be involved in back awareness. A total of 264 individuals with CLBP and 128 healthy controls (HC) answered an online survey, including the FreBAQ-S, and questions regarding the completeness, comprehensibility, time-to-complete adequacy, and time spent completing it. If participants declared a lack of completeness, they had to report which aspects would be incorporated into the questionnaire to explore additional back-awareness-related variables. A statistically significant difference in completeness emerged between groups (p < 0.01). The questionnaire was comprehensible for more than 85% of participants, regardless of the group (p = 0.45). CLBP participants spent significantly more time in completing the questionnaire than controls (p < 0.01), but no differences were found between groups regarding the time-to-complete adequacy (p = 0.49). Regarding the back-awareness-related variables, 77 suggestions from CLBP group and seven from the HC were received. Most of them were related to proprioceptive acuity such as posture, weight, or movement patterns, among others. The FreBAQ-S demonstrated adequate face/content validity, completeness, comprehensibility, and adequate time of response. The feedback provided will help improve currently available assessment tools.